Can a health information exchange save healthcare costs? Evidence from a pilot program in South Korea. Issue 9 (September 2015) - Park, Hayoung; Lee, Sang-il; Hwang, Hee; Kim, Yoon; Heo, Eun-Young; Kim, Jeong-Whun; Ha, Kyooseob
Highlights We assess impacts of HIE on utilization at a tertiary hospital following referrals. We found savings in total charges in the HIE group. Savings were mostly found in diagnostic tests and imaging. However, savings were not seen in drugs, outpatient visits and hospital stays. Physicians had access to more clinical information for HIE than non-HIE patients.